2019
DOI: 10.3389/fmars.2019.00294
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Priorities for Shark Conservation in the Bay of Bengal, Bangladesh

Abstract: Fisheries bycatch is known as the major threat to Threatened shark species (herein, sharks, skates, and rays) in Bangladesh. But bycatch is not appropriately addressed under the existing wildlife and fisheries conservation management regime. This policy brief evaluates the current scenario of shark conservation and identifies priorities for future interventions. The literature review finds 71 shark species and only four peerreviewed publications from Bangladesh suggesting the species already known have not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Previous estimations of elasmobranch diversity in Bangladeshi waters have been significantly underestimated (35 to 81 in different studies) [ 34 , 35 , 71 , 74 , 77 , 80 , 83 , 84 , 86 , 91 , 92 ]. By recording artisanal catch, the study has raised the number of reported elasmobranch species in Bangladesh by thirteen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous estimations of elasmobranch diversity in Bangladeshi waters have been significantly underestimated (35 to 81 in different studies) [ 34 , 35 , 71 , 74 , 77 , 80 , 83 , 84 , 86 , 91 , 92 ]. By recording artisanal catch, the study has raised the number of reported elasmobranch species in Bangladesh by thirteen.…”
Section: Discussionmentioning
confidence: 99%
“…Most significantly, they receive limited conservation actions due to data deficiency, lack of community awareness, facilitation in taking sustainable approaches, and finally, resource constraints. Bangladesh remains a conspicuous data gap regarding a comprehensive understanding of its elasmobranch diversity and catches despite being a highly fished region [ 41 , 50 , 70 , 72 – 74 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Human population growth leads to a concomitant demand for shark products locally [23] and internationally [24].…”
Section: Agenda Settingmentioning
confidence: 99%
“…Oceanography & Fisheries Open access Journal traded [41]. The Ministry of the Environment, Forests, and Climate Change is working assiduously to implement our country's strong commitment to international accords for wildlife conservation [42].…”
Section: Sharks and Rays Conservation In Bangladeshmentioning
confidence: 99%